WHAT TRANSLATION TELLS US ABOUT MOTION: A CONTRASTIVE STUDY OF TYPOLOGICALLY DIFFERENT LANGUAGES - Ibarretxe, Iraide (International Journal of English Studies, 2003)
Slobin (1991, 1996a,b, 1997) has argued that the typological differences between languages with either a satellite-framed or a verb-framed lexicalisation pattern (Talmy, 2000) have important discourse and rhetorical consequences for the expression of ’paths of movement’ and ’manner of movement’. These differences are especially significant for the translator since s/he has to adapt the rhetorical style of the source language to that of the target language. According to Slobin (1996a, 2000, ms.), the major difference lies in the loss or gain of information about path and manner specifications during the translation process.We will focus on three languages, English (satellite-framed), Spanish and Basque (both verb-frarned but with important intratypological differences). Basing ourselves on data from translations of the same English text (Tolkien’s The Hobbit) into these two target languages, we will compare and analyse in detail the different strategies that Spanish and Basque translators follow when adapting the English text to the stylistic and typological characteristics of their own languages.